The Mongolian Agricultural Industry. Possibility in Logistics Supply-Chain - Otgonbileg Khasar (2020)
Mongolian food supply system has significantly impacted consumers by disconnecting consumers and local food manufactures, increasing safety of food risk and tonne-kilometres. The environment and demand for locally manufactured good has been positively affected by the supply system. However, due to high logistics costs, local food suppliers do not have enough competitive room with wide-ranging food supply systems. The overall goal of this thesis is to make food supply chain logistics management more efficient. The thesis consists of: a) Problems with food trackability. b) Analysis of the supply and allocation of animal meat on small and large stockyards. c) Collaboration and regional integration into the local food delivery system. d) Installation of gathering centres and the formation of collaboration and network integration and further integration into a wide-ranging of agricultural goods delivery systems. One of the most important tools considered as a necessary part of the food logistics system is an effective food tracking system. It enables all the food supply-chain management to be unified. The negative impact of local food supply systems on the environment could be lowered as result to reduce transport distance, number of vehicles and to increase efficient use of vehicle capacity. Research has shown that the incorporated logistic network can improve food tracking, logistic efficiency, economic benefits, future marketing networks, food quality and safety, suppliers' competitiveness, weakening negative environmental impacts, and fostering sustainable local food systems.